An Overview of Differences Between Types of Chimeras and Their Impact on Humans - Kaabi , Zahraa S. M. Al; Hassan, Ghofran F. Abdul; Hassan, Lina A.; Hammood, Samah Amer (Journal for Research in Applied Sciences and Biotechnology, 2023)
Chimera has several important definitions that are common to each other, where he is known a single creature that is made up of two or more separate populations of genetically unique cells that originated from various zygotes. Definition can be interpreted as cells from one person might appear in another individual in a process known as chimerism. These cells may be incorporated into the parenchyma or they may circulate. Chimeras are divided into several types depending on several factors such as the percentage of chimera cells in the body of the organism neighborhood, origin, or other reasons, which includes microchimeras, natural human macro-chimeras and man-made chimeras. Chimeric cells in human can arise from three significant sources, namely originating from gestation, blood transfusions, and transplants.